Analisis Pengendalian Kualitas Produk Keramik di PT Perkasa Primarindo - Harjoprayitmo, Weni Wijatmiko (Universitas Pamulang, 2023)
This analysis focuses on the use of the Six-Sigma and Kaizen methods to find out the work processes by PT PERKASA PRIMARINDO that caused defects in their tile products and then formulate actions to reduce the number of defects and is thus expected to increase the quantity of quality products. The analysis results in a DPMO value of 464.1488, or equivalent to a Sigma level of 4.81. As the perfect DPMO value is 3.4 (equivalent to Sigma 6 level), this shows that PT Perkasa Primarindo still has the opportunity to improve the quality of iheir tile products. The p-chart shows the proportion of defects that are unstable and outside the upper control limit (UCL) and lower control limit (LCL) during production in 2020. Furthermore, from the analysis it is also known that there were two main causes of defects, namely the over-temperature of HD dryer, and a poor cleanliness. With these findings, an action procedure has been proposed through the Kaizen method which is expected to control the quality of tile products so that they are still within the threshold value.